Copper Deficiency Myeloneuropathy Resembling B12 Deficiency: Partial Resolution of MR Imaging Findings with Copper Supplementation - Goodman, B.P.; Chong, B.W.; Patel, A.C.; Fletcher, G.P.; Smith, B.E. (American Journal of Neuroradiology, 2006)
SUMMARY: Copper deficiency has been associated with a clinical syndrome, myeloneuropathy. Radiographic changes resembling B12 deficiency in the cervical spinal cord have been described. We present a case of copper deficiency myeloneuropathy, with cervical MR imaging findings resembling B12 deficiency, which partially reversed following copper supplementation. This is, to our knowledge, the first described case of radiographic improvement with copper supplementation.